Penjatuhan Kebiri Kimia Bagi Pelaku Kejahatan Seksual Terhadap Anak Dalam Perspektif Falsafah Pemidanaan - S, Tunggal; Naibaho, Nathalina (UI Scholars Hub, 2023)
Sexual assault against children is an phenomenon that often occurs in Indonesia. The statistic shows that the number of sexual assault against children doesn't decrease significantly. Punishment is not the only way to control the number of sexual assault against children. Then, the goverment passed new regulation that regulating of chemical castration in hope of reducing the number of sexual crimes against children. However, the presence of chemical castration raises objections and differences of opinion in various circles. This research aims to determine the sentencing purpose of chemical castration and the proper sanction for imposing chemical castration in Indonesia. This research is a normative study using documentary studies in the form of secondary data with interviews as a complement. The research was found that the purpose of punishment from chemical castration was for rehabilitation, with notes that the chemical castration treatment is dropped for the sexual offender against children with pedophilia.